Az alexandriai zsidóság hatalomhoz való viszonya a Példabeszédek könyve Septuaginta-fordításának tükrében - Csalog, Eszter (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
It is not typical to draw conclusions from a translation regarding an ancient social and political issue. However, I will attempt to do it in this paper: on the basis of one of the most freely translated book of the Septuagint, the Paroimiai (Greek version of the Proverbs), I will try to get an answer to the question of how certain Jewish intellectuals saw the problem of proper relationship to pagan rulers in Alexandria in the second century Bc. As an introduction, I will outline the main events of the Jews’ stay in Egypt from the sixth century Bc to the Ptolemaic Age. Subsequently I will illustrate through some characteristic examples how far the translators went within the Torah if they wanted to update the text. Turning to the Paroimiai, I will show the most important features of the Greek text through some typical examples. Finally, I will present the passages where the attitude towards the king as well as the right behavior in civil life is concerned. One can clearly recognize the tendency that loyal relationship as well as the avoidance of riots or conflicts are even more emphasised in the Greek version. From this point of view, the text of the Paroimiai is unique; no similar tendency can be noticed in any of the Septuagint books, and this is only partly due to content reasons.